KONVERSI LAHAN DAN STRUKTUR PRODUKSI KEBUN: STUDI KASUS TERBENTUKNYA PERKEBUNAN KELAPA SAWIT RAKYAT PADA DUA DESA SAWAH ETNIS SERAWAI DAN JAWA DI KABUPATEN SELUMA, PROPINSI BENGKULU - Widiono, Septri (Jurnal AGRISEP, 2008)
Estate small landholders of palm oil were developed by converting wetland area. This research was aimed to study conversion of wetland area into palm oil estate, to study palm oil estate profile of farmers, and to formulate the structure of estate production. This research used survey method combining with indepth interviews. Sixty respondents were selected using simple random sampling method and data were analysed using an analytical description. The finding of this research showed that land conversion occurs due to decreasing village economic under wetland agricultural system. Palm oil estate farmers profile differs between two villages, namely Pasar Seluma (Serawai ethnic) and Rawasari (Java ethnic) in terms of land ownership, productivity, and labour relation. Finally, the production structure were also significantly difference with wetland agricultural system in which the  estate agricltural system close to the structure of oil palm industry.